2006
DOI: 10.1097/00061198-200604000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Findings in Pigment Dispersion Syndrome and Pigmentary Glaucoma

Abstract: Loss of trabecular cells, fusion of trabecular lamellae with collapse of intertrabecular spaces, increase in extracellular material, and obliteration of the canal were found in various amounts around the circumference of eyes with pigment dispersion syndrome and elevated intraocular pressure, and pigmentary glaucoma. These probably all contribute to the development of increased intraocular pressure. Meshworks from trabeculectomy specimens showed these findings and also showed artifactual damage of cells and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
50
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 26 publications
11
50
1
1
Order By: Relevance
“…Genes for cell motility were significantly upregulated, possibly reflecting migration of TM cells into Schlemm's canal, as has been reported in human PG 9,27 . We observed a decline in cell-matrix adhesions and an altered cytoskeleton, as reported in another study 67 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Genes for cell motility were significantly upregulated, possibly reflecting migration of TM cells into Schlemm's canal, as has been reported in human PG 9,27 . We observed a decline in cell-matrix adhesions and an altered cytoskeleton, as reported in another study 67 .…”
Section: Discussionsupporting
confidence: 69%
“…We developed a porcine eye model of PG that replicates clinical features including pigment granules in the aqueous humor 8 and inside of TM cells 9,27,28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigment treatment has previously been shown to cause ocular hypertension in part by reorganizing the TM actin cytoskeleton and not by physical obstruction of the outflow tract 7,21 . We have recently reported that long, thick, and continuous TM actin bundles emerge as early as 24 hours after pigment exposure 3 and replicate this observation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…TM cells are gradually lost throughout life in all individuals and, under normal circumstances, they are not replaced (15). A number of studies have demonstrated that loss of TM cells is higher in POAG patients than in age-matched controls (16)(17)(18). The effects of lower TM cellularity are currently unclear, but it has been proposed that reduced TM cellularity, or the functional decline of surviving TM cells, engenders a reduced ability to maintain TM homeostasis and causes structural aberrations within the TM.…”
mentioning
confidence: 99%